Pattern of head injury in central India population - Pate, Rajeshwar S.; Hire, Rohan C.; Rojekar, Mohit V. (International Journal of Research in Medical Sciences, 2017)
Background: In India, the developing economy and growing population simultaneously made a strong impact on increase in motor vehicle population. This increase in motorization has some adverse effects such as increase in road accidents with economic and functional loss. Head injury is the most common cause of mortality in road traffic accidents. The aim of this study was to know the incidence, pattern, mechanism, mode of head injury along with its distribution in relation to site of vault fracture and intracranial hemorrhage. Methods: Total 391 post-mortem cases of head injury were enrolled during study period. The information regarding age, sex, residence, marital status, date and time of time of accident and of death was gathered from police inquest report, relatives, dead body challan and clinical details from hospital records. During autopsy, detailed examination was carried out and data regarding both external and internal injuries were carefully recorded and analyzed. Results: The peak incidence of head injury was observed in the age group of 21-30 years. Most of deceased were from early age group and the male deceased were more than females. Majority victims of head injury were from road Traffic Accidents followed by fall from height, railway accidents and assault. Fissured fracture of vault was found in almost half cases. Subdural and subarachnoid hemorrhage were the most common one we encountered. Conclusions: Head injury due to RTA is well known public health problem causing death and disability. It is required from concerned government authority to take appropriate and immediate measures for reducing the incidence of head injury.